Boolean and Spatial Analysis Using GIS to Determine Landfill Waste on Bunaken Island with an Environmental Health Approach - Birawida, Agus Bintara; Daud, Anwar; Mallongi, Anwar; R Silalahi, Steven; Sila, Nurlia; Todingan, Melisa (Universitas Airlangga, 2024)
Introduction: Bunaken Island still lacks proper waste management infrastructure, resulting in the accumulation of garbage around residences and along the coastline. This prevalent issue significantly impacts public health and the overall quality of life on the island. The research seeks to evaluate the waste management situation on Bunaken Island and identify suitable locations for waste disposal. Methods: The study employed random sampling techniques to select households within the study area for primary data collection. The research utilized Boolean and spatial analysis methods to pinpoint appropriate waste disposal zones and propose sustainable waste management strategies for Bunaken Island. Results and Discussion: Findings revealed that Bunaken Island spans a land area of 794.12 hectares and is inhabited by a population of 3,843. The analysis identified two recommended locations for final disposal zones, totaling 3.40 and 0.45 hectares, respectively. Moreover, the estimated waste generation over the next decade is approximately 4,277,893 kilograms, necessitating 0.0241 hectares of land for waste accommodation through terracing methods. Conclusion: Addressing this issue requires the identification of two viable disposal zones in distinct locations. Additionally, implementing recycling practices to utilize both organic and inorganic waste from local and marine sources and promoting reuse before landfill disposal are crucial strategies for effective waste management on Bunaken Island.